2023
DOI: 10.18203/2394-6040.ijcmph20230247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention deficit hyperactivity disorder in the Arab Gulf countries: systematic review and meta-analysis

Abstract: Attention deficit hyperactivity disorder (ADHD) is an important growing psychiatric health problem of children and adolescents all over the world. This review aimed to investigate the prevalence of ADHD in the Arab Gulf countries. A literature search was conducted on 14 January 2022. Any paper reporting the prevalence of ADHD in Arab Gulf countries was included. R software was used for the meta-analysis. We included 14 papers. The prevalence of ADHD was 5.90% (95% confidence interval (CI)=1.73-20.14). We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The overall prevalence of ADHD in the current meta-analysis (10.3%) aligns closely with previous studies conducted in Arab and African populations,9 14 15 100 which reported a range of ADHD prevalence between 1.3% and 16%. However, these previous studies did not pool the data from Iran or Israel and did not include a large sample size like in this current study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall prevalence of ADHD in the current meta-analysis (10.3%) aligns closely with previous studies conducted in Arab and African populations,9 14 15 100 which reported a range of ADHD prevalence between 1.3% and 16%. However, these previous studies did not pool the data from Iran or Israel and did not include a large sample size like in this current study.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent systematic review, Aljadani et al reported that the prevalence of ADHD among Saudis was 12.4% 14. Additionally, three previous studies estimated the prevalence of ADHD in Arab Gulf countries, Arab countries and Africa between 5.9% and 10.5% 9 14 15. Despite these accumulated evidence and variations in ADHD estimated prevalence, it is well known that its prevalence might be influenced by various factors such as gender, culture, environment, socioeconomic status and demographics 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have found a wide range of con icting estimates of the prevalence of ADHD (Almojarthe, 2023). According to Polanczyk et al's most recent meta-analysis study, which comprised 41 studies from 27 different countries, the worldwide prevalence of ADHD in children and adolescents is 3.4% (Polanczyk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have found a wide range of conflicting estimates of the prevalence of ADHD [ 16 ]. According to Polanczyk et al's most recent meta-analysis study, which comprised 41 studies from 27 different countries, the worldwide prevalence of ADHD in children and adolescents is 3.4% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%